Analysis of Fluidity and Flow Characteristics of A356 Aluminum in Sand Casting Using Numerical Simulation Method - Andri Willy Adianta (Trigin Publisher, 2021)
Aluminum silicon alloy is an aluminum alloy that is widely used in engineering. This alloy has good strength and is widely produced into components through the casting process. Silicon content can lead to a decrease in the fluidity of aluminum castings which in turn will reduce the quality of castings, this fluidity is also influenced by the temperature at which molten aluminum is poured. This study aims to determine the effect of pouring temperature on fluidity, flow characteristics and casting defects in aluminum silicon alloy casting using sand molds. Casting is done by gravity casting, simulation flow analysis includes the distribution of flow velocity, temperature, pressure, surface defects and fluidity that occur during the process of filling the mold cavity and the comparison of the fluidity of castings and surface defects in the experimental. Pouring temperatures of 685, 710, 735, 760 and 785°C with 1, 3, 5, 7, 9, and 12 mm pattern mold thicknesses. The simulation process uses computational fluid dynamic based software. The results obtained that the pouring temperature of 785oC has the highest flow velocity of ±0.145 m/s in a 12mm cavity and a high temperature distribution of ±759oC in a 3mm cavity, while the pouring temperature of 685oC has a high pressure distribution of ±107287 Pa in the cavity. 6mm. Surface defects that occur at least at a temperature of 685oC. The best casting fluidity is at a temperature of 785oC where the cavities of 12, 9, 7, 5 and 3 mm are fully filled and 1mm reaches 181.4 mm.